Development of Binaural Sensitivity: Eye Gaze as a Measure of Real-time Processing - Peng, Z. Ellen; Kan, Alan; Litovsky, Ruth Y. (Frontiers in Systems Neuroscience, 2020)
Children localize sounds using binaural cues when navigating everyday auditory environments. While sensitivity to binaural cues reaches maturity by 8-10 years of age, large individual variability has been observed in the just-noticeable-difference (JND) thresholds for interaural time difference (ITD) among children in this age range. To understand the development of binaural sensitivity beyond JND thresholds, the “looking-while-listening” paradigm was adapted in this study to reveal the real-time decision-making behavior during ITD processing. Children ages 8-14 years with normal hearing (NH) and a group of young NH adults were tested. This novel paradigm combined eye gaze tracking with behavioral psychoacoustics estimating ITD JNDs in a two-alternative forced-choice discrimination task. Results from simultaneous eye gaze recordings during ITD processing suggested that children had adult-like ITD JNDs, but they demonstrated immature decision-making strategies. While the time-course of arriving at the initial fixation and final decision in providing a judgment of the ITD direction was similar, children exhibited more uncertainty than adults during decision-making. Specifically, children made more fixation changes, particularly when tested using small ITD magnitudes, between the target and non-target response options prior to finalizing a judgment. These findings suggest that, while children may exhibit adult-like sensitivity to ITDs, their eye gaze behavior reveals that the processing of this binaural cue is still developing through late-childhood.